Pengaruh Brand Identity Dan Food Quality Terhadap Loyalitas Pelanggan (Studi Pada Rumah Makan Rocket Chicken Di Kabupaten Majalengka) - Fauzi, Haris; Suparto, L; Monica, Tita (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2025)
In a franchise business, the franchisor provides a developed way of doing business, providing guidance, systems and ongoing assistance in exchange for payment of fees and/or periodic purchases. This includes franchise-based restaurant and eatery businesses in the culinary industry. This research aims to determine the influence of brand identity and food quality on customer loyalty at Rocket Chicken restaurants in Majalengka Regency. The research method used is a survey method with a descriptive verification approach. The data source is primary data, which was collected using a questionnaire. The research population is customers of Rocket Chicken restaurants whose exact number is not known. The research sample was taken randomly using an accidental sampling technique and consisted of 100 respondents. Data analysis techniques were carried out using multiple linear regression tests, partial tests, model feasibility tests, and classical assumption tests including normality tests, multicollinearity tests, heteroscedasticity tests and autocorrelation tests. The research results show that the model consisting of the independent variables brand identity and food quality is suitable for predicting customer loyalty. Partially, both brand identity and food quality have a positive and significant influence on customer loyalty at Rocket Chicken restaurants.